Achieving sustainable development goals through corporate social responsibility and responsiveness in Zimbabwe: achievements, challenges, and future opportunities - Zenda, Mashford; Zhanda, Kelvin; Dzvimbo, Munyaradzi A. (Frontiers in Sustainability, 2025)
Discussions on multi-stakeholder participation in Sustainable Development Goals (SDGs) has often framed sustainability knowledge exchanges in the corporate world. As SDG number 17 outlines the role of partnerships/stakeholders, both developed and developing countries have embraced Corporate Social Responsibility (CSR) as a stakeholder’s tool for achieving SDGs. However, many studies have shunned examination on how CSR has been harnessed by large enterprises in developing countries such as Zimbabwe towards implementing SDGs. To address this knowledge gap, we examine the engagement dynamics through a case study analysis of three enterprises in Zimbabwe (Tongaat Hulett, Econet Wireless and Delta Corporation) working on development projects with communities to attaining SDGs. A qualitative research approach was adopted, involving in-depth interviews with three representatives (one from each enterprise) and analysis of secondary data from corporate annual reports. Results from the study indicates progress has been made by these enterprises in achieving the SDGs coupled with consistence on sustainability reporting. It emerged that these enterprises CSR are not at the advanced phase of SDG implementation. While they are conscious and responsive to several SDGs that respond to the socio-economic and environmental demands of the communities they operate in, their CSR strategy is partly focused to the SDGs. Policy environment and lack of clear CSR benchmarks in the country hinder the smooth operation of CSR which in turn, draws back the attainment of SDGs targets set by enterprises. Therefore, the study recommends that CSR efforts on SDGs should be anchored on inter-enterprises partnerships and continuous sustainability reporting and monitoring. The SDGs model offers an opportunity for the corporate world to contribute to sustainable development in Zimbabwe.